PROSEDUR PEMBUKAAN REKENING DEPOSITO PADA BANK BAPAS PUSAT 69 - Salma Arjuan Yumna Firmansyah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to determine the technique of opening and disbursing closing deposit accounts at BPR BAPAS 69 Magelang Head Office. The method in this study is Descriptive Analysis by defining, illustrating, or summarizing data points so that patterns that meet all data conditions can emerge. The results of this study are that the customer must come to the BAPAS 69 BPR office bringing the requirements (KTP/SIM/PASPOR/KITAS and NPWP), visit the Customer Service counter, submit the required files, and fill out a form for opening a BPR BAPAS 69 deposit account at the Head Office Magelang. As for deposits, filling out deposit slips, deposits at teller counters, and collecting deposits at Customer Service counters are examples of deposit procedures. Complete the KTP/SIM/PASPOR/KITAS and NPWP withdrawal requirements, bring a photocopy of one of the requirements and a stamp along with the deposit slip to the Customer Service counter, fill out the deposit withdrawal form, pay a fine if it is not due, and go to the teller counter to withdraw money at the time BPR BAPAS 69 deposit account disbursement procedure, Magelang Head Office.